Child-Protection Systems – Summary - Jakab, Nóra; Benyusz , Márta (Child-Protection Systems, 2025)
Abstract:In this comparative chapter we identify the best practices at the European and international level regarding child protection systems and conduct an in-depth and transparent analysis of these would provide an opportunity for countries to improve their child protection system. Such a multidimensional approach can lead to the removal of inefficient practices and the creation of an integrated, functional system. The child protection system shall be based on preventive, corrective and other protection measures adopted by the competent state authorities in terms of social welfare services and material support for the child and his/her family. Protection measures are taken by the competent administrative or judicial authorities in cases where state intervention is required owing to deficiencies in the exercise of parental responsibility or in order to take a decision on the care of a child without parental custody. The entire system of child protection shall rest on the idea of appropriate application of what is in the child’ best interests. This principle is applied when choosing the type of support and assistance for the child and his or her parents or caregivers, regarding all decisions concerning alternative care, as well as for determining the most suitable measures for the child leaving alternative care. Keywords: child protection system, alternative care, best practices, country specific issues, integrated system